Biomasa de Cornops aquaticum (Orthoptera: Acrididae) en humedales del nordeste de Argentina - Gallardo, Luciana Irene (2015)
Biomass of Cornops aquaticum (Orthoptera: Acrididae) in wetlands of Northeast Argentina. The estimation of biomass in insect populations is a key factor to quantify the available resources and energy fluxes in ecosystems food webs. Cornops aquaticum is a common herbivore in Eichhornia plants in wetlands of Northeast Argentina. We aimed to analyse its biomass variation, related to the different grasshopper age categories populations in two host-plants: Eichhornia azurea and Eichhornia crassipes. For this, standard samplings of C. aquaticum populations were carried out with an entomological net of 70cm diameter in two wetlands with E. azurea and E. crassipes, in Corrientes and Chaco Provinces; besides, dry weight was also obtained (directly and indirectly), and a regression model to indirectly estimate the biomass from a linear dimension measure (hind femur length) is proposed. A total of 2 307 individuals were collected and separated in different age categories; their abundance and linear dimension data were obtained. The model proposed was lnDM=lna+b*lnH (where DM=dry mass, a and b are constants and H=hind femur length) (R2=0.97). The population biomass variations of C. aquaticum were due to the relative abundance of each age category and the grasshopper individual dry weight. No significant differences were found between populations biomasses obtained by direct and indirect methods in E. azurea and E. crassipes floating meadows. This model made easier the C. aquaticum biomass calculation for both individuals and the population, and accelerated the processing of high number of samples. Finally, high biomass values of populations and individual age category (especially in adults) emphasize the importance of C. aquaticum as a consumer and a resource for predators on Eichhornia floating meadows food webs.